Critique and disclosure : critical theory between past and future - Kompridis, Nikolas (MIT Press, 2006)
A provocatively argued call for shifting the emphasis of critical theory from Habermasian "critique," restricted to normative clarification, to "disclosure," a possibility-enhancing approach that draws on and reinterprets ideas of Heidegger.